One-way moisture-conducting micro / nano fiber membrane and centrifugal spinning preparation method thereof

Preparation of SBS fiber membranes through centrifugal spinning and plasma modification technology solves the problem of water discharge difficulties in traditional clothing in high humidity environments, achieves efficient moisture evaporation and comfort improvement, simplifies the process and reduces the environment and health risk.

CN119221205AActive Publication Date: 2024-12-31ZHEJIANG SCI-TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411591378.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-31
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Traditional one-way wet clothing is difficult to discharge moisture absorbed by fibers in high humidity environments, and the preparation process is complex and poses potential risks to the environment and human health.

Method used

The SBS fiber membrane was prepared by centrifugal spinning technology, and the superhydrophilic fiber membrane was constructed through plasma gas-liquid grafted hydrophilic monomer and hot pressing composite method to improve the water evaporation rate and comfort.

Benefits of technology

Simplifies the process, reduces the risk to the environment and human health, improves wear comfort, and provides better elasticity and functionality for sportswear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221205A_ABST
    Figure CN119221205A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional micro / nano fiber preparation, and particularly relates to a one-way moisture-conducting micro / nano fiber membrane and a centrifugal spinning preparation method thereof. A polymer and a solvent are mixed and centrifugally spun, and a porous fiber membrane product is obtained by rapidly volatilizing the solvent to form holes. A high-power light source is used for irradiation in the spinning process, the light source directly irradiates a spinning nozzle and sprayed fibers, the temperature of the spinning environment is rapidly increased in the irradiation process, volatilization of a solvent on the fibers after the fibers are formed is accelerated, and the porous structure of the fibers can be constructed easily; according to the preparation method, an SBS porous membrane contains hydroxyl radicals through low-temperature cold plasma modification, the SBS porous membrane and acrylamide are subjected to free radical graft polymerization under the protection of nitrogen, the SBS porous membrane is endowed with super hydrophilicity, and then the one-way moisture-conducting fiber membrane is prepared in a hot-pressing compounding mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional micro / nano fiber preparation, and specifically relates to a unidirectional moisture-conducting micro / nano fiber membrane and a centrifugal spinning preparation method thereof. Background Art

[0002] Traditional one-way moisture-conducting clothing on the market currently mainly uses cotton and polyester as raw materials, which are favored for their softness and good moisture absorption. However, these traditional fabrics have obvious deficiencies in water evaporation rate, resulting in reduced comfort for wearers in high humidity environments. In addition, the preparation process of these fabrics is relatively complicated, and a large amount of hydrophilic / hydrophobic finishing agents are required during the hydrophobic modification process, which not only increases production costs, but may also have adverse effects on the environment and human health.

[0003] In order to solve the above problems, new functional fiber membranes prepared based on centrifugal spinning technology are gradually becoming a new choice for the industry. SBS (styrene-butadiene-styrene block copolymer), as a thermoplastic elastomer with excellent performance, has attracted attention for its perfect combination of high elasticity, strength and thermoplasticity. The SBS fiber membrane is grafted with hydrophilic monomers through plasma gas-liquid induction, and then hot-pressed to composite the original membrane, which effectively increases the water evaporation rate and improves wearing comfort. This preparation method not only simplifies the process flow, but also reduces potential risks to the environment and human health.

[0004] The good elasticity of SBS fiber membrane makes it more in line with the characteristics of sportswear, providing the wearer with a better sports experience. Compared with traditional fabrics, these improvements of SBS fiber membrane give it broad application prospects in the field of functional clothing. With the improvement of environmental protection and health awareness, SBS fiber membrane is expected to become an effective alternative to traditional unidirectional moisture-conducting fabrics due to its potential in reducing environmental pollution and improving wearing comfort. Summary of the invention

[0005] The purpose of the present invention is to provide a unidirectional moisture-conducting micro / nano fiber membrane, which is constructed by centrifugal spinning and hydrophilic modification, thereby solving the technical defect that the moisture absorbed by the fibers of traditional unidirectional moisture-conducting clothing is difficult to discharge in a hot and humid environment.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] A centrifugal spinning method for preparing a unidirectional moisture-conducting micro / nano fiber membrane, the method comprising the following steps:

[0008] (1) Centrifugal spinning: The polymer is mixed with a solvent and dispersed evenly to obtain a spinning solution, wherein the mass concentration of the polymer is 20wt%-24wt%;

[0009] The polymer is a mixture of one or more of the following organic polymer materials: styrene-butadiene-styrene triblock copolymer (SBS), linear triblock copolymer (SEBS), polystyrene-polyisoprene-polystyrene triblock copolymer (SIS);

[0010] The solvent is a mixture of one or more of the following solvents: water, N-N-dimethylformamide (DMF), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dichloromethane (DCM), and dichloroethane (DCE);

[0011] The prepared spinning solution is used for centrifugal spinning. During the spinning process, a high-power light source of 1000W-1500W is used for irradiation. The light source is directly irradiated on the spinneret and the ejected fibers. During the irradiation process, the spinning environment temperature is rapidly increased, which accelerates the volatilization of the solvent on the fibers after the fibers are formed, and constructs a porous fiber structure; a polymer micro / nano fiber membrane is obtained;

[0012] (2) Low-temperature cold plasma modification: The prepared polymer micro / nano fiber membrane is placed in a cold plasma modification treatment apparatus for oxygen plasma modification glow discharge treatment, with a treatment pressure of 40Pa±5Pa, a treatment power of 80W±10W, and a treatment time of 100s-140s;

[0013] (3) Preparation of super hydrophilic fiber membrane: The fiber membrane treated by cold plasma is hydrophilically modified in an acrylamide (AM) solution;

[0014] (4) Preparation of unidirectional moisture-conducting fiber membrane: The polymer micro / nano fiber membrane obtained in step (1) and the super-hydrophilic fiber membrane obtained in step (3) are composited by hot pressing to obtain a unidirectional moisture-conducting micro / nano fiber membrane.

[0015] The principle of the present invention is: a polymer and a solvent are mixed and centrifugally spun, and a porous fiber membrane product is obtained by using the solvent to volatilize rapidly to form holes. During the spinning process, a high-power light source is used for irradiation, and the light source directly irradiates the spinneret and the ejected fibers. During the irradiation process, the spinning environment temperature is rapidly increased, which accelerates the volatilization of the solvent on the fibers after the fibers are formed, which is beneficial to the construction of a porous fiber structure; the SBS porous membrane contains hydroxyl radicals through low-temperature cold plasma modification, and the SBS porous membrane and acrylamide undergo free radical graft polymerization under the protection of nitrogen, giving the SBS porous membrane super-hydrophilicity, and then a one-way moisture-conducting fiber membrane is prepared by hot pressing and compounding.

[0016] Preferably, in step (1), the spinning solution consists of solute SBS and solvent DCM, and the mass fraction of SBS in the spinning solution is 20 wt%.

[0017] Preferably, during centrifugal spinning in step (1), the diameter of the spinning hole is 0.4 mm and the spinning speed is 8000 rpm / min.

[0018] Preferably, in step (2), the oxygen purity is 99.99%, the plasma treatment pressure is 40 Pa, the power is 80 W, and the time is 120 s.

[0019] Preferably, in step (3), the concentration of acrylamide (AM) in the AM solution is 10wt%-15wt%; the fiber membrane is subjected to hydrophilic modification grafting treatment under nitrogen protection, the hydrophilic modification temperature is 60-80°C, and the time is 15-45min.

[0020] Preferably, in step (3), the concentration of acrylamide (AM) in the AM solution is 10 wt %; the hydrophilic modification temperature is 80° C., and the time is 45 min.

[0021] Preferably, in step (4), the heat pressing and laminating equipment is a heat press machine, the laminating temperature is 90° C., and the time is 10 seconds.

[0022] Preferably, the thickness of the polymer micro / nano fiber membrane prepared in step (1) is 0.2 mm±0.01 mm.

[0023] Preferably, during the centrifugal spinning in step (1), the light source is provided by a news light, the color temperature of the news light is 2800-5600K, and the power is 1300W.

[0024] A unidirectional moisture-conducting micro / nano fiber membrane prepared by the preparation method.

[0025] The present invention uses the water resistance and elasticity of styrene-butadiene-styrene block copolymer (SBS) to construct a unidirectional moisture-conducting fiber membrane through centrifugal spinning and hydrophilic modification. The present invention uses a gas-liquid plasma modification method to prepare a super-hydrophilic fiber membrane, and then uses a hot pressing method to prepare an asymmetric wetting unidirectional moisture-conducting fiber membrane. The key point (difficulty) lies in the regulation of the thickness of the hydrophobic side fiber membrane, which is a key factor affecting the unidirectional moisture-conducting effect.

[0026] Compared with the prior art, the present invention has the following significant advantages: high centrifugal spinning yield, simple and easy-to-operate equipment, and fiber regulation can be adjusted by controlling process parameters such as rotation speed, spinning solution concentration, spinneret aperture, and collecting rod distance to obtain the required fiber diameter and different specific surface areas. The SBS porous membrane is pretreated by oxygen plasma and then grafted with acrylamide (AM) monomer, and finally composited with an unmodified SBS porous membrane. The prepared fiber membrane has excellent unidirectional moisture conduction effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1is a SEM image of the SBS fiber membrane after grafting acrylamide (AM) monomer in Example 1-5;

[0028] Figure 2 is a SEM image of the SBS fiber membrane after grafting acrylamide (AM) monomer in Example 6;

[0029] Figure 3 It is the grafting rate of the monomer at different grafting times and a grafting temperature of 80°C. DETAILED DESCRIPTION

[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0032] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0033] Centrifugal spinning machine (Simeco Intelligent Manufacturing Co., Ltd.), styrene-butadiene-styrene block copolymer (SBS, Kraton, USA), dichloromethane (DCM, analytical grade, Hangzhou Gaojing Fine Chemical Co., Ltd.), acrylamide (AM, analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.);

[0034] Cold plasma treatment instrument, HD-1 type, Changzhou Changtai Plasma Technology Development Co., Ltd. The cold plasma treatment instrument comprises a vacuum chamber, a radio frequency power generator, a pressure indicator and an automatic timing alarm.

[0035] High power news light, The color temperature is 2800-5600k and the power is 1300W.

[0036] The centrifugal spinning device used in centrifugal spinning includes a motor, a spinning head and a collecting rod. The spinning head is installed on the top of the motor's rotating shaft and is driven to rotate by the motor. The spinning head has a cavity for accommodating spinning liquid, a liquid injection port is provided on the top of the spinning head, and a spinneret hole connected to the cavity is provided on the side wall of the spinning head. The collecting rod is arranged around the spinning head.

[0037] During centrifugal spinning, the spinning speed is adjusted to 8000rpm / min, and a high-power light source is used for irradiation. The light source is directly irradiated on the spinneret and the ejected fibers, and the porous micro / nano fiber membrane is obtained by receiving it through a collecting rod. During the irradiation process, the spinning environment temperature rises rapidly, which accelerates the volatilization of the solvent on the fiber after the fiber is formed, which is conducive to the construction of a porous fiber structure.

[0038] Example 1

[0039] A centrifugal spinning preparation method for a unidirectional moisture-conducting micro / nano fiber membrane, the specific steps are as follows:

[0040] (1) Use an analytical balance to accurately weigh the polymer: 2g styrene-butadiene-styrene block copolymer (SBS) and the solvent: 8g dichloromethane (DCM), place them in a 20ml sample bottle, seal the sample bottle with raw tape, and stir at room temperature for 4h to finally obtain a spinning solution with uniform SBS dispersion. The obtained spinning solution is injected into the spinneret of a centrifugal spinning machine, and then In high power news light Under irradiation Perform centrifugal spinning to obtain a SBS porous membrane;

[0041] (2) Wash and dry the SBS porous membrane to obtain a smooth fiber membrane surface. Then attach the prepared SBS porous membrane to a glass plate and place it in the vacuum chamber of a cold plasma treatment instrument; turn on the power switch, evacuate the vacuum chamber, control the pressure in the vacuum chamber to 10Pa, and introduce oxygen, reflux 2-3 times. Adjust the gas valve to control the pressure in the vacuum chamber to 40Pa, turn on the plasma RF power button, and after the plasma discharges, turn on the timing button, the processing time is 120s, the power is 80w, close the oxygen valve and then turn off the power.

[0042] (3) Accurately weigh 10 g of acrylamide (AM) using an analytical balance, place it in a 250 ml beaker, add 90 g of deionized water, heat to 60 °C, then place the plasma-treated SBS porous membrane in the working solution, graft under nitrogen protection for 45 min, take it out, rinse it with anhydrous ethanol, and then dry it at 60 °C.

[0043] (4) The untreated SBS porous membrane and the SBS fiber membrane grafted with acrylamide monomer are composited by a hot pressing composite method to obtain a unidirectional moisture-conducting fiber membrane.

[0044] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 7kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.5kg / m 2 / d.

[0045] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 630, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -530.

[0046] Example 2

[0047] A centrifugal spinning preparation method for a unidirectional moisture-conducting micro / nano fiber membrane, the specific steps are as follows:

[0048] (1) Use an analytical balance to accurately weigh the polymer: 2g styrene-butadiene-styrene block copolymer (SBS) and the solvent: 8g dichloromethane (DCM), place them in a 20ml sample bottle, seal the sample bottle with raw tape, and stir at room temperature for 4h to finally obtain a spinning solution with uniform SBS dispersion. The obtained spinning solution is injected into the spinneret of a centrifugal spinning machine, and then In high power news light Under irradiation Perform centrifugal spinning to obtain a SBS porous membrane;

[0049] (2) Wash and dry the SBS porous membrane to obtain a smooth fiber membrane surface. Then attach the prepared SBS porous membrane to a glass plate and place it in the vacuum chamber of a cold plasma treatment instrument; turn on the power switch, evacuate the vacuum chamber, control the pressure in the vacuum chamber to 10Pa, and introduce oxygen, reflux 2-3 times. Adjust the gas valve to control the pressure in the vacuum chamber to 40Pa, turn on the plasma RF power button, and after the plasma discharges, turn on the timing button, the processing time is 120s, the power is 80w, close the oxygen valve and then turn off the power.

[0050] (3) Accurately weigh 10 g of acrylamide (AM) using an analytical balance, place it in a 250 ml beaker, add 90 g of deionized water, heat to 70 °C, then place the plasma-treated SBS porous membrane in the working solution, graft under nitrogen protection for 45 min, take it out, rinse it with anhydrous ethanol, and then dry it at 60 °C.

[0051] (4) The untreated SBS porous membrane and the SBS fiber membrane grafted with acrylamide monomer are composited by a hot pressing composite method to obtain a unidirectional moisture-conducting fiber membrane.

[0052] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 7.5kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.4kg / m 2 / d.

[0053] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 700, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -600.

[0054] Example 3

[0055] A centrifugal spinning preparation method for a unidirectional moisture-conducting micro / nano fiber membrane, the specific steps are as follows:

[0056] (1) Use an analytical balance to accurately weigh the polymer: 2g styrene-butadiene-styrene block copolymer (SBS) and the solvent: 8g dichloromethane (DCM), place them in a 20ml sample bottle, seal the sample bottle with raw tape, and stir at room temperature for 4h to finally obtain a spinning solution with uniform SBS dispersion. The obtained spinning solution is injected into the spinneret of a centrifugal spinning machine, and then In high power news light Under irradiation Perform centrifugal spinning to obtain a SBS porous membrane;

[0057] (2) Wash and dry the SBS porous membrane to obtain a smooth fiber membrane surface. Then attach the prepared SBS porous membrane to a glass plate and place it in the vacuum chamber of a cold plasma treatment instrument; turn on the power switch, evacuate the vacuum chamber, control the pressure in the vacuum chamber to 10Pa, and introduce oxygen, reflux 2-3 times. Adjust the gas valve to control the pressure in the vacuum chamber to 40Pa, turn on the plasma RF power button, and after the plasma discharges, turn on the timing button, the processing time is 120s, the power is 80w, close the oxygen valve and then turn off the power.

[0058] (3) Accurately weigh 10 g of acrylamide (AM) using an analytical balance, place it in a 250 ml beaker, add 90 g of deionized water, heat to 80 °C, then place the plasma-treated SBS porous membrane in the working solution, graft for 45 min under the protection of nitrogen, take it out, rinse it with anhydrous ethanol, and then dry it at 60 °C.

[0059] (4) The untreated SBS porous membrane and the SBS fiber membrane grafted with acrylamide monomer are composited by a hot pressing composite method to obtain a unidirectional moisture-conducting fiber membrane.

[0060] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 9kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.3kg / m 2 / d.

[0061] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1300, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -1250.

[0062] Example 4

[0063] This example prepares a unidirectional moisture-conducting fiber membrane, which is different from Example 3 only in that the grafting time is 15 minutes.

[0064] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 5kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.5kg / m 2 / d.

[0065] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 450, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -400.

[0066] Example 5

[0067] This example prepares a unidirectional moisture-conducting fiber membrane, which is different from Example 3 only in that the grafting time is 30 minutes.

[0068] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 7kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.5kg / m 2 / d.

[0069] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 965, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -900.

[0070] Example 6

[0071] This embodiment prepares a unidirectional moisture-conducting fiber membrane, which is different from the embodiment 3 only in that the grafting temperature is 90° C. and the grafting time is 45 min.

[0072] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 8kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.4kg / m 2 / d.

[0073] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1000, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -800.

[0074] Example 7

[0075] This example prepares a unidirectional moisture-conducting fiber membrane, which is different from Example 3 only in that the grafting time is 60 minutes.

[0076] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 8.8kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.4kg / m 2 / d.

[0077] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1265, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -1000.

[0078] Comparative Example 1

[0079] This comparative example prepares a unidirectional moisture-conducting fiber membrane, which is different from Example 3 in that it is not treated in step (2). Its performance is tested under standard conditions.

[0080] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.6kg / m 2 / d.

[0081] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 150, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -20.

[0082] Comparative Example 2

[0083] This comparative example prepares a unidirectional moisture conducting material, which differs from Example 3 in that nitrogen protection is not used in step (3). Its performance is tested under standard conditions.

[0084] According to the national standard GB / T12704.2-2009 positive cup method, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 6kg / m 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.6kg / m 2 / d.

[0085] According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 930, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -750.

[0086] in conclusion

[0087] In step (3) of Example 1-5, different grafting temperatures and times were used to prepare the fiber membranes, namely 60°C 45 min, 70°C 45 min, 80°C 45 min, 80°C 15 min, and 80°C 30 min. The SEM images of the SBS fiber membranes after grafting acrylamide (AM) monomers in Example 1-5 are shown in FIG. Figure 1 The grafting rate of acrylamide monomer on the fiber surface prepared at 60℃ for 45min in Example 1 is very low. The acrylamide monomer prepared at 70℃ for 45min in Example 2 begins to form a relatively complete monomer film on the fiber surface. The fiber surface grafting effect prepared at 80℃ for 45min in Example 3 is the best.

[0088] Figure 2 is a SEM image of the SBS fiber membrane after grafting acrylamide (AM) monomer in Example 6, the grafting temperature is 90°C, the grafting time is 45min, according to Figure 2 It can be seen that when the grafting temperature is 90°C, damage begins to appear on the surface of the fiber membrane, affecting the mechanical properties of the fiber.

[0089] Figure 3 is the grafting rate of the monomer at different grafting times at a grafting temperature of 80°C. The only difference between Example 6 and Example 3 is that the grafting time is 60 minutes. Figure 3 It can be seen that the grafting rate of the monomer does not change significantly as the grafting time continues to increase.

[0090] Through scanning electron microscope (SEM) image observation, we found that when the grafting temperature was 60°C and the time was 45 minutes, the grafting effect of acrylamide on SBS fiber was not ideal. When the temperature was raised to 70°C, a monomer film began to cover the surface of SBS fiber, and when the temperature was further raised to 80°C, the grafting success rate increased significantly. This result is attributed to the enhanced interaction between the monomer and the fiber surface at high temperature, which improves the efficiency of the free radical reaction, and the grafting rate gradually increases with time. Therefore, the grafting temperature of 85°C and the time of 45 minutes are preferred as the optimal processing parameters.

[0091] From the above test results, it can be seen that the unidirectional moisture-conducting micro / nano-fiber membrane prepared in Example 3 has the best effect, and its moisture permeability flux (from the hydrophobic layer to the hydrophilic layer) is the highest, reaching 9 kg / m 2 / d, while the moisture permeability (from the hydrophilic layer to the hydrophobic layer) is the lowest, only 0.3kg / m 2 / d. At the same time, its one-way transfer index (hydrophobic layer to hydrophilic layer) is also the highest, reaching 1300, while the one-way transfer index (hydrophilic layer to hydrophobic layer) is the lowest, at -1250. In Example 3, the grafting time of acrylamide (AM) is 45 min and the temperature is 80°C, which is conducive to a more complete grafting reaction, thereby improving the hydrophilicity of the fiber membrane.

[0092] Example 8 Single factor test for thickness control of SBS porous membrane

[0093] The preparation of SBS porous membrane is the same as in Example 3, and the specific steps are as follows: Use an analytical balance to accurately weigh the polymer: 2g styrene-butadiene-styrene block copolymer (SBS), solvent: 8g dichloromethane (DCM), put them in a 20ml sample bottle, seal the sample bottle with raw tape, stir at room temperature for 4h to finally obtain a spinning solution with uniform SBS dispersion. The obtained spinning solution is injected into the spinneret of a centrifugal spinning machine, and then Under the high-power news lights Centrifugal spinning was performed to obtain a SBS porous membrane.

[0094] This example discusses the thickness of the SBS porous membrane as a single factor and tests its performance under standard conditions.

[0095] When the thickness of the SBS porous membrane is 0.10 mm, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 9.5 kg / m according to the positive cup method of GB / T12704.2-2009. 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 6.5kg / m 2 / d. According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1000, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is 600.

[0096] When the thickness of the SBS porous membrane is 0.15 mm, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 9 kg / m according to the positive cup method of GB / T12704.2-2009. 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 4.3kg / m 2 / d. According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1130, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is 450.

[0097] When the thickness of the SBS porous membrane is 0.2 mm, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 9.3 kg / m according to the positive cup method of GB / T12704.2-2009. 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.2kg / m 2 / d. According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 1350, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -1300.

[0098] When the thickness of the SBS porous membrane is 0.25 mm, the moisture permeability of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 0.25 kg / m according to the positive cup method of GB / T12704.2-2009. 2 / d, the moisture permeability from the hydrophilic layer to the hydrophobic layer is 0.3kg / m 2 / d. According to the national standard GB / T21655.2-2019, the one-way transfer index of the fiber membrane from the hydrophobic layer to the hydrophilic layer is 0, and the one-way transfer index from the hydrophilic layer to the hydrophobic layer is -1200.

[0099] In Example 8, we explored the effect of hot-pressed untreated SBS porous membranes of different thicknesses on unidirectional moisture conduction performance. The results showed that when the thickness of the SBS porous membrane was 0.1 mm and 0.15 mm, although the fiber membrane had a good ability to transfer water from the hydrophobic layer to the hydrophilic layer, the water transferred to the hydrophilic layer easily flowed back to the hydrophobic layer due to the small thickness of the hydrophobic layer, and the prepared fiber membrane had poor unidirectional transfer performance. When the thickness of the SBS porous membrane increased to 0.2 mm, the fiber membrane had the best unidirectional moisture conduction performance, and its moisture permeability (hydrophobic layer to hydrophilic layer) was the highest, reaching 9.3 kg / m 2 / d, while the moisture permeability (from the hydrophilic layer to the hydrophobic layer) is the lowest, only 0.2kg / m 2 / d. At the same time, its one-way transfer index (hydrophobic layer to hydrophilic layer) is also the highest, reaching 1350, while the one-way transfer index (hydrophilic layer to hydrophobic layer) is the lowest, at -1300. When the thickness of the SBS porous membrane is 0.25mm, water can only stay on the hydrophobic side of the fiber membrane and cannot penetrate to the hydrophilic side, and the fiber membrane completely loses its one-way moisture conduction ability.

[0100] In summary, when the thickness of the SBS porous membrane is 0.2 mm, the effect of the prepared unidirectional moisture-conducting micro / nanofiber membrane is the best, achieving efficient unidirectional moisture-conducting performance.

[0101] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0102] The above is a detailed introduction to a unidirectional moisture-conducting micro / nano fiber membrane and a centrifugal spinning preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A centrifugal spinning method for preparing a unidirectional moisture-conducting micro / nanofiber membrane, characterized in that The method comprises the following steps: (1) Centrifugal spinning: The polymer is mixed with a solvent and dispersed evenly to obtain a spinning solution, wherein the mass concentration of the polymer is 20wt%-24wt%; The polymer is a mixture of one or more of the following organic polymer materials: styrene-butadiene-styrene triblock copolymer (SBS), linear triblock copolymer (SEBS), polystyrene-polyisoprene-polystyrene triblock copolymer (SIS); The solvent is a mixture of one or more of the following solvents: water, N-N-dimethylformamide (DMF), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dichloromethane (DCM), and dichloroethane (DCE); The prepared spinning solution is used for centrifugal spinning. During the spinning process, a high-power light source of 1000W-1500W is used for irradiation. The light source is directly irradiated on the spinneret and the ejected fibers. During the irradiation process, the spinning environment temperature is rapidly increased, which accelerates the volatilization of the solvent on the fibers after the fibers are formed, and constructs a porous fiber structure; a polymer micro / nano fiber membrane is obtained; (2) Low-temperature cold plasma modification: The prepared polymer micro / nano fiber membrane is placed in a cold plasma modification treatment apparatus for oxygen plasma modification glow discharge treatment, with a treatment pressure of 40Pa±5Pa, a treatment power of 80W±10W, and a treatment time of 100s-140s; (3) Preparation of super hydrophilic fiber membrane: The fiber membrane treated by cold plasma is hydrophilically modified in an acrylamide (AM) solution; (4) Preparation of unidirectional moisture-conducting fiber membrane: The polymer micro / nano fiber membrane obtained in step (1) and the super-hydrophilic fiber membrane obtained in step (3) are composited by hot pressing to obtain a unidirectional moisture-conducting micro / nano fiber membrane.

2. The preparation method according to claim 1, characterized in that: In step (1), the spinning solution consists of solute SBS and solvent DCM, and the mass fraction of SBS in the spinning solution is 20wt%.

3. The preparation method according to claim 1, characterized in that: During centrifugal spinning in step (1), the diameter of the spinning hole is 0.4 mm and the spinning speed is 8000 rpm / min.

4. The preparation method according to claim 1, characterized in that: In step (2), the oxygen purity is 99.99%, the plasma treatment pressure is 40 Pa, the power is 80 W, and the time is 120 s.

5. The preparation method according to claim 1, characterized in that: In step (3), the concentration of acrylamide (AM) in the AM solution is 10wt%-15wt%; the fiber membrane is subjected to hydrophilic modification grafting treatment under nitrogen protection, the hydrophilic modification temperature is 60-80°C, and the time is 15-45min.

6. The preparation method according to claim 1, characterized in that: In step (3), the concentration of acrylamide (AM) in the AM solution is 10 wt %; the hydrophilic modification temperature is 80° C. and the time is 45 min.

7. The preparation method according to claim 1, characterized in that: In step (4), the hot pressing and laminating equipment is a heat press machine, the laminating temperature is 90° C., and the time is 10 seconds.

8. The preparation method according to claim 1, characterized in that: The thickness of the polymer micro / nano fiber membrane prepared in step (1) is 0.2 mm ± 0.01 mm.

9. The preparation method according to claim 1, characterized in that: During the centrifugal spinning in step (1), the light source is provided by a news light, the color temperature of the news light is 2800-5600K, and the power is 1300W.

10. A unidirectional moisture-conducting micro / nano fiber membrane prepared by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Centrifugal spinning preparation method for micro-nano fiber membrane

    CN105543990A

  • Multi-dimensional hydrophilic and hydrophobic structure composite nano-fiber membrane and preparation method thereof

    CN109731483A

  • Preparation method of multilevel-structure one-way moisture-conducting waterproof and breathable film

    CN112481831A

  • Selective water vapour transport membranes comprising a nanofibrous layer and methods for making the same

    WO2012167366A1

  • Spinning stock solution, and heat-resistant creep-resistant fiber and preparation method therefor

    WO2022156215A1